Indications for and outcome of open AAA repair in the endovascular era. - Hoffmann-Wieker, Carola Marie; Spazier, Max; Böckler, Dittmar (The journal of cardiovascular surgery, 2016)
Abstract: The benefits, safety and efficacy of endovascular aortic aneurysm repair (EVAR) is well documented and intensively reported in multiple...
Gesehen am 25.11.2019